Considering the Baptism of Edgardo Mortara in the Context of Catholic Teachings and Rituals Then and Now - Turner, Paul (Studies in Christian-Jewish Relations, 2019)
The baptism of one-year old Edgardo Mortara by a maid in his parental home in 1852 took place at an age when Catholics believed that salvation came only to those baptized, when the baptism of children was usually celebrated during a lengthy, complex ritual led by a priest at the parish church, yet when the church allowed and encouraged others - even laity - to perform baptism when, in their judgment, an emergency had arisen. Although the contemporary Catholic Church has modified these beliefs and practices, permissions and rules still govern the emergency baptism of children, even those of non-Christian parents.